The objectives of this research are: (1) To analyze labor structural transformation in West Java Province, (2) To analyze linkage intersector on labor structure transformation process interfarm, industry and other sectors, (3) To analyze impact of fiscal decentralization on economic growth and labor structure transformation in West Java Province. In order to answer the above, a simultaneous equation model was established, consisting of 32 structural equations and 15 identity equations. Further - Muhammad Arief Dirgantoro; Sjafri Mangkuprawira; Hermanto Siregar; Bonar M. Sinaga (Forum Pasca Sarjana, 2010)
The objectives of this research are: (1) To analyze labor structural transformation in West Java Province, (2) To analyze linkage intersector on labor structure transformation process interfarm, industry and other sectors, (3) To analyze impact of fiscal decentralization on economic growth and labor structure transformation in West Java Province.  In order to answer the above, a simultaneous equation model was established, consisting of 32 structural equations and 15 identity equations.  Furthermore, this research used data pooling where data were analyzed with descriptive analysis, econometrics model, as well as predictions using a variety of policy scenario alternatives.  Model was then estimated by 2SLS method with SYSLIN procedures, while prediction simulation was performed by using SIMNLIN procedures.  In its development era, West Java province have done transformation structure of labor.  During this labor structure transformation process, the decrease on agricultural sector contribution was not automatically followed by increase in labor contribution in industrial sector since it was absorbed by other sectors such as the informal ones.  The increase in local taxes receipt gave a positive impact on output growth, but it had a negative impact on agriculture labor, and it had lead to labor structure transformation.  The result also showed that an increase in personel current expenditure and regional income from DAU gave a positive impact on agriculture output growth and it had not lead to labor  structure transformation.  Next, the increase development expenditure for agriculture gave a positive impact on output growth agriculture, but it had a negative impact on total output growth and it had not lead to labor structure transformation.  Expenditure for infrastructure had a positive impact on output growth, and it had lead to labor structure transformation.   Key words: fiscal decentralization policy, economic growth, labor structure transformation, simultaneous equation model